The increased volatility of the stocks markets against the background of instability of financial market - S. I. Tarakanov (Путеводитель предпринимателя)
In this article the behavior of the main stock indixes of the USA and the Russian indices of MICEX from 2018 to fall of 2019 is investigated. The increased volatility of indexes is found. In general, it is a consequence of instability of world financial markets. In turn, the main role is played here by war of duties between the USA and China.